Eclipse - Meyer, Stephenie (New York : Little, Brown and Company, 2007)
Bella must choose between her friendship with Jacob and her relationship with Edward, but when Seattle is ravaged by a mysterious string of killings, the three of them need to decide whether their personal lives are more important than the well-being of an entire city.
Keywords: Vampires -- Fiction; Fantasy fiction